O futuro do emprego sob a ótica de uma nova migração de riquezas entre nações à luz de um mundo globalizado: um debate entre Paul Kennedy e Domenico de Masi - Graff, Alexandre de Miranda (2004)
The final objective of this work will be to develop a study collating the theses defended for the historian Paul Kennedy and sociologist Domenico De Masi, presenting the ma in factors that influence in the process of migration of the jobs for the developed countries or in its maintenance in the countries in development, verifying if it has signals of flexibility in such process as reply to the fast technological development andl or the expansion of the 'creative leisure'. The present work has for purpose to search not them last and projected taxes of growth of work, but yes the factors that appear less in the threshold of related centuries XX and XXI to the human work and a possible route of migration of the existing jobs in the developed countries for the nations richest of the planet what it would lead, for consequence, to a still bigger inequality it enters the poor nations richest and, leading to a social collapse caused by the aggravation of the inequality in this distribution of income between the peoples.